Pengembangan Media Pembelajaran Pada Mata Pelajaran IPS Materi Potensi Sumber Daya Alam Di Indonesia Kelas VII SMP Negeri 2 Ampel - Hardiani, Irma, Drs. Dahroni, M.Si (2015)
The study aims to review the initials develop and produce medium-Based Learning That Shaped CD multimedia learning materials Natural Resources in Indonesia. ALSO initial study aimed to determine the effectiveness of the review of the Product hearts to help and Facilitate peamahaman Students Against materials Natural Resources in Indonesia. This study is a research Label Development. The product is developed multimedia learning Natural Resources in Indonesia The berbetnuk CD. Model Development Research & Development Research Methods hearts is: (1) Needs Analysis (2) Development Planning (3) Product Development (4) Initial Product (5) Evaluation (6)End Products. Product development has been validated Posted Baharudin Mr. Saiful Anwar as Media Expert and Mrs. Ari Diniyati As material expert. Subject trials hearts Research is a Class VII student of SMP. Test Learning Media Development Natural Resource in Indonesia initials done in SMP Negeri 2 Ampel. Data Analysis Techniques Used Research hearts husband is a descriptive quantitative analysis technique. Results that show: (1) Media Used Shaped CD Format hearts tutorial hearts type of branched That give s freedom for Students for a review determines Direction learning and (2) Learning Media multimedia-based eye Lessons IPS hearts Shape CD Learning Natural Resources in Indonesia Class VII considered feasible to use the Learning hearts.